CRAN-17. TUMOUR COMPARTMENT TRANSCRIPTOMICS DEMONSTRATE THE ACTIVATION OF INFLAMMATORY AND ODONTOGENIC PROGRAMMES IN HUMAN ADAMANTINOMATOUS CRANIOPHARYNGIOMA AND IDENTIFY NOVEL THERAPEUTIC TARGETS. Issue 2 (22nd June 2018) - Apps, John; Guiho, Romaine; Hong, Ying; Hargrave, Darren; Brogan, Paul; Jacques, Thomas; Martinez-Barbera, Juan Pedro
Abstract: Adamantinomatous Craniopharyngiomas (ACPs) are challenging sellar region tumours, known to be characterised by mutations in CTNNB1. ACPs are often histologically complex, with different morphological cell types and surrounded by reactive glial tissue. Murine models, generated through activating β-catenin, support a critical role for nucleo-cytoplasmic accumulating β-catenin cell clusters ('clusters') in driving tumorigenesis. We performed RNA-Seq, with and without laser capture microdissection, of human ACP to develop cell type specific molecular signatures. We integrate this with RNA-Seq data from two ACP mouse models to reveal that cell clusters are molecularly analogous to the enamel knot, a critical signalling centre controlling normal tooth morphogenesis. Supporting this finding, we show that human cluster cells express high levels of several members of the FGF, TGFB and BMP families of secreted factors, which signal to neighbouring cells as evidenced by immunostaining against the phosphorylated proteins pERK1/2, pSMAD3 and pSMAD1/5/9 in both human and mouse ACP. We reveal that inhibiting the MAPK/ERK pathway with a clinically approved MEK inhibitor results in the reduction of proliferation and increased apoptosis in explant cultures of human and mouse ACP. Finally, we analysed a prominent molecular signature in the glial reactive tissue to characterise the inflammatory microenvironment and uncover the activation of inflammasomes in human ACP. We validated these results by immunostaining, ELISA and proteomic analysis in both solid tumour and cystic fluid from ACP patients. Our data support a new molecular paradigm for understanding ACP tumorigenesis as an aberrant mimic of natural tooth development and opens new therapeutic opportunities.